2020
DOI: 10.1186/s12860-020-00317-7
|View full text |Cite
|
Sign up to set email alerts
|

IL6/sIL6R regulates TNFα-inflammatory response in synovial fibroblasts through modulation of transcriptional and post-transcriptional mechanisms

Abstract: Introduction The clinical efficacy of specific interleukin-6 inhibitors has confirmed the central role of IL6 in rheumatoid arthritis (RA). However the local role of IL6, in particular in synovial fibroblasts (SF) as a direct cellular target to IL6/sIL6R signal is not well characterized. The purpose of the study was to characterize the crosstalk between TNFα and IL6/sIL6R signaling to the effector pro-inflammatory response of SF. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Importantly, the combined treatment with TGF-β and IL-1β resulted in a significant (**p=0.0047) increase in ICAM-1 expression compared with IL-1β only treated synovial fibroblasts (figure 8A). Fibroblasts are the main source of IL-6 in RA with pro-inflammatory synovial fibroblast secreting high levels of IL-6 in response to TNF-α 6 37. Similarly to the expression of ICAM-1, treatment of synovial fibroblasts with TGF-β did not lead to increased IL-6 secretion compared with untreated synovial fibroblasts, however the combined treatment with TGF-β and IL-1β resulted in a significant (**p=0.0018) increase in IL-6 compared with IL-1β only treated synovial fibroblasts (figure 8B).…”
Section: Resultsmentioning
confidence: 93%
“…Importantly, the combined treatment with TGF-β and IL-1β resulted in a significant (**p=0.0047) increase in ICAM-1 expression compared with IL-1β only treated synovial fibroblasts (figure 8A). Fibroblasts are the main source of IL-6 in RA with pro-inflammatory synovial fibroblast secreting high levels of IL-6 in response to TNF-α 6 37. Similarly to the expression of ICAM-1, treatment of synovial fibroblasts with TGF-β did not lead to increased IL-6 secretion compared with untreated synovial fibroblasts, however the combined treatment with TGF-β and IL-1β resulted in a significant (**p=0.0018) increase in IL-6 compared with IL-1β only treated synovial fibroblasts (figure 8B).…”
Section: Resultsmentioning
confidence: 93%
“…A previous study showed MK2 was involved in regulating the TNF-induced expression of IL-8 by p38 MAPK in human lung microvascular endothelial cells at a post-transcriptional level (Su et al, 2008). Another study showed the stimulation of synovial fibroblasts with IL-6 and TNF-a cooperatively inhibited the induction of IL-8 (Valin et al, 2020). It was speculated that a more complex mechanism in IL-8 secretion existed induced by coaggregation of F. nucleatum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…PsA is a chronic immune-mediated rheumatic disease. Studies have reported that the posttranscriptional regulation of gene expression plays a vital role in rheumatic disease ( 26 , 27 ). However, most studies have focused on microRNA and related pathways, while only a few focused on the mRNA surveillance pathway ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%